2018
DOI: 10.1007/s40556-018-0169-z
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of Isolated Redundant Foramen Ovale: A Case Report

Abstract: Redundant foramen ovale (RFO) is defined as an abnormally redundant foramen ovale flap that extends at least halfway across the left atrium. The exact pathogenesis is unknown. Premature, isolated, in utero RFO is rare. The prevalence in general population is unknown as it may be easily ignored on routine fetal echocardiography. The reported frequency in fetuses referred for echocardiographic examination is 0.6-1.7%. It can cause right ventricular volume overload leading to fetal hydrops and subsequent cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…In normal fetal hearts, a RFOF has been reported to occur in roughly one third of the cases with a restrictive FO 7 . Restrictive FO has been investigated widely in the presence of CHD, because of the association with poor fetal and neonatal outcome 1–4 , while its occurrence in normal fetal hearts and in association with RFOF has been reported less often 5–10 . The fact that ventricular disproportion might occur in cases with RFOF but without evidence of a restrictive FO was not evident from these studies 5–9 and has been described only rarely 10 .…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In normal fetal hearts, a RFOF has been reported to occur in roughly one third of the cases with a restrictive FO 7 . Restrictive FO has been investigated widely in the presence of CHD, because of the association with poor fetal and neonatal outcome 1–4 , while its occurrence in normal fetal hearts and in association with RFOF has been reported less often 5–10 . The fact that ventricular disproportion might occur in cases with RFOF but without evidence of a restrictive FO was not evident from these studies 5–9 and has been described only rarely 10 .…”
Section: Introductionmentioning
confidence: 85%
“…Restrictive FO has been investigated widely in the presence of CHD, because of the association with poor fetal and neonatal outcome [1][2][3][4] , while its occurrence in normal fetal hearts and in association with RFOF has been reported less often [5][6][7][8][9][10] . The fact that ventricular disproportion might occur in cases with RFOF but without evidence of a restrictive FO was not evident from these studies [5][6][7][8][9] and has been described only rarely 10 . This possibly causal relationship is of importance, because ventricular disproportion is one of the indirect sonographic signs possibly associated with coarctation of the aorta (CoA) [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…An isolated RFOF is rare and easily overlooked in prenatal ultrasound examinations. The incidence of isolated RFOF detected by ultrasonography is only 0.6-1.7% [9,10]. To date, only two cases of prenatal diagnosis have been reported, including one case by Hagen et al [9] and one by Devadasan et al [10].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately one-third of isolated RFO have a redundant foramen ovale ap (RFOF) [7]. Fetuses with isolated RFOF have better outcomes than those with isolated RFO, but few studies have explored the ultrasonographic features of RFOF [8][9][10]. In addition, some studies have shown that the ultrasonographic features of RFOF are similar to those of aortic coarctation (CoA), which often leads to a false positive diagnosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…CoA has been classically defined as a narrowing of the aorta in the region of the ligamentum arteriosum (11), representing a spectrum of aortic narrowing from a discrete constriction of the AOi to tubular hypoplasia, with many variations between these two extremes (12) The exact pathogenesis of RFOF remains unclear, but it may be related to a localized developmental abnormality (13) or intrauterine myocarditis (14). RFOF is associated with several congenital malformations, including fetal hydrops and atrial arrhythmias (15).…”
Section: Discussionmentioning
confidence: 99%